Karakats: the Bricolage of Hybrid Vehicles that Skate and Swim - Patrick Laviolette; Alla Sirotina (Journal of Ethnology and Folkloristics)
This paper explores the material culture of ‘karakat’ (Russian karakatitsa) hybrid vehicles in the town of Kallaste, east Estonia. It focuses on the social factors that allow karakat culture to change. The region of study was part of the Soviet Union so the phenomenon of self-assembled vehicles implies socialist and communist considerations. Local people are still surrounded by the material legacy of that time. Technological assemblages from the past therefore continue to live in the present. It was popular in the USSR to maintain off-road vehicles, which were put together with the owner’s own hands. Such a bricolage technique has been preserved since the middle of the 20th century and is something that is used as a marker of local identity. The distribution of spare parts was problematic in former Soviet times and this has influenced the way men now make karakats. Current owners spend a lot of time servicing their vehicles. The issue of masculinity is highly relevant here because dealing with technology is seen as a masculine activity. Moreover, because it is increasingly open to tourists, karakat culture is becoming a tradable commodity.